Motivational strategies to create a good environment in english class - Hurtado Jorque, Vilma Margoth (2016)
One of the most important factors in the English language is to achieve a good motivation because it is essential for language learning in the classroom. However, lack of motivational strategies, demotivate students causing an unpleasant learning environment for English language. The objective of this research was: to analyze motivational strategies to create a good environment in the English class. The research was descriptive because it provides detailed information regarding the importance of motivational strategies in teaching English. Furthermore, it has a quantitative approach. Therefore, a survey was applied to students at ninth year of the Delia Ibarra de Velasco Educative Unit during the academic period 2015-2016 in order to collect data about the use of motivational strategies. In addition, a survey was applied to teachers of English to obtain data about the application of the motivational strategies in the English class....